Bank Digital Syariah: Inovasi Teknologi Finansial Berbasis Prinsip Islam di Era Ekonomi Digital - Afifah Ammanda (Lembaga Yasin AlSys, 2025)
Digital transformation in the banking sector has garnered significant attention; however, studies specifically examining the integration of sharia principles in the development of digital Islamic banks remain limited. This study aims to analyze the digitalization processes undertaken by Islamic banking institutions in Indonesia and assess the extent to which financial technology innovations can be implemented without compromising Islamic legal principles. A descriptive qualitative approach was employed using a document analysis design, based on secondary data from the Financial Services Authority (OJK), the National Committee for Islamic Economy and Finance (KNEKS), academic publications, and the annual reports of Islamic banks from 2020 to 2025. Content and thematic analysis methods were used to identify patterns, strategies, and the implications of digitalization within the context of Islamic economics. The findings reveal that digitalization significantly contributes to asset growth and operational efficiency in Islamic banks, while also fostering institutional consolidation that strengthens industry structure. The success of digital Islamic banks depends not only on technological adoption but also on their ability to align innovation with sharia principles, such as justice, transparency, and the prohibition of riba. The integration of Islamic values and technology results in a business model that is both adaptive and ethical. These findings expand the application of the Diffusion of Innovations theory within Islamic economic contexts and affirm that technology can serve as a tool to reinforce sharia values in the digital era. Practical implications highlight the need for regulatory support and the enhancement of digital capacity within Islamic financial institutions to ensure sustainable innovation. This study also opens avenues for further research on customer experiences and the effectiveness of digital oversight by the Sharia Supervisory Board in ensuring compliance with Islamic principles amid technological transformation.